2020
DOI: 10.1155/2020/3590389
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Inflammatory Markers Are Inversely Associated with Heart Rate Variability Measures in Type 1 Diabetes

Abstract: Introduction. A neuroimmune communication exists, and compelling evidence suggests that diabetic neuropathy and systemic inflammation are linked. Our aims were (1) to investigate biomarkers of the ongoing inflammation processes including cytokines, adhesion molecules, and chemokines and (2) to associate the findings with cardiovascular autonomic neuropathy in type 1 diabetes by measuring heart rate variability and cardiac vagal tone. Materials and Methods. We included 104 adults with type 1 diabetes. Heart rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…For instance, it has been shown that anticoagulative medications decrease the risk of thromboembolism in diabetes [34], the triglyceride-glucose index is associated with the risk of stroke [35], and adiponectin is associated with major adverse cardiovascular events [36]. Neither of these was measured in this study, we have, however, previously shown an association between adiponectin with heart rate variability measures in type 1 diabetes [37]. Fourthly, a large proportion of the cohort used antihypertensive medication, including β-blockers, which may affect the study results.…”
Section: Table 3 Associations Adjusted For Demographic Factors Diabetes Factors and Cardiovascular Risk Factorscontrasting
confidence: 64%
“…For instance, it has been shown that anticoagulative medications decrease the risk of thromboembolism in diabetes [34], the triglyceride-glucose index is associated with the risk of stroke [35], and adiponectin is associated with major adverse cardiovascular events [36]. Neither of these was measured in this study, we have, however, previously shown an association between adiponectin with heart rate variability measures in type 1 diabetes [37]. Fourthly, a large proportion of the cohort used antihypertensive medication, including β-blockers, which may affect the study results.…”
Section: Table 3 Associations Adjusted For Demographic Factors Diabetes Factors and Cardiovascular Risk Factorscontrasting
confidence: 64%
“…ICAM-1 can produce soluble ICAM-1 through alternative splicing, which can be measured in various body fluids [ 9 ]. Studies have shown that ICAM-1 levels are elevated in atherosclerosis, cardiovascular disease, and metabolic vascular neuropathy [ 10 13 ]. However, there are still few studies on the correlation between ICAM-1 and AIS.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, lower RSA correlated with increased inflammation-related cytokines (most strongly TNFa, but also IL-6, IL1a and IFNg; not with CRP). Relationships between heart rate variability and cytokines have been reported earlier in patients with a broad range of diseases such as those with heart failure (Malave et al, 2003;Nikolic et al, 2013), obesity and diabetes (Parish et al, 2016;Wegeberg et al, 2020), obstructive sleep apnea (Xie et al, 2020), infants with hypoxic ischemic encephalopathy (Al-Shargabi et al, 2017;Yasova Barbeau et al, 2019), in traumatic brain injury (Deepika et al, 2018), to name just a few, and in larger samples of healthy subjects (Cooper et al, 2015;Lampert et al, 2008;von Kanel et al, 2008). Note that all papers cited demonstrated a low-HRV-associated-with-high-cytokines relationship, although not always using the same measures for HRV/cytokines, but according to a recent meta-analysis, SDNN and HF-HRV should show the largest effect sizes (Williams et al, 2019).…”
Section: Discussionmentioning
confidence: 83%